What do we know about nonprofit collaboration? A systematic review of the literature - Gazley, Beth; Guo, Chao (Nonprofit management & leadership, 2020)
This systematic literature review reports on the content of past empirical studies of nonprofit collaboration within and across the sectors, published between 1972 and 2015 (n = 657). An analysis of these articles reveals four major themes: diverse but “siloed” data; imbalance in research coverage; the dominance of “big four” organization theories; and limited improvement in research sophistication. It further identifies five specific research gaps: the insufficient attention to the forms and intensity of nonprofit collaboration; the divergences and contradictions in theoretical reasoning and empirical evidence; the lack of attention to the moderators and/or mediators of collaboration; the lack of understanding of collaborative failure; and the lack of comparative studies. These findings help to inform collaboration research and practice by observing the value in using a broader scope of literature and methods to build knowledge in this area.